2021
DOI: 10.3390/nu13010165
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins and Flavan-3-Ols in the Prevention and Treatment of Periodontitis—Antibacterial Effects

Abstract: Flavan-3-ols and their oligomeric forms called proanthocyanidins are polyphenolic compounds occurring in several foodstuffs and in many medicinal herbs. Their consumption is associated with numerous health benefits. They exhibit antioxidant, anti-inflammatory, cytoprotective, as well as antimicrobial activity. The latter property is important in the prevention and treatment of periodontal diseases. Periodontitis is a multifactorial polymicrobial infection characterized by a destructive inflammatory process aff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Although the ESI-MS (Figure 6) and UV-HPLC (Figure 7) chromatograms of all extracts seem very similar in quality, there are differences, especially in quantity of compounds. Some of the compounds-mainly those belonging to anthraquinones and phenylpropanoids (corresponding peak numbers in the parentheses): emodin-glucoside (29), torachrysone-hexoside (32), emodin-glucoside (33), emodin-8-O-(6 -O-malonyl)-glucoside (34), unknown torachrysone derivative (35), emodin bianthrone-hexose-(malonic acid)-hexose (38), hydropiperoside (39), and vanicoside B (48)-were abundant only in the 60% acetone extract, while being observed only in trace amounts in the 40% EtOH or in 25% EtOH. HMDB ID: The Human Metabolome Database, Physcion*-observed only in the positive mode.…”
Section: Hplc/dad/esi-hr-tof-ms Qualitative and Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ESI-MS (Figure 6) and UV-HPLC (Figure 7) chromatograms of all extracts seem very similar in quality, there are differences, especially in quantity of compounds. Some of the compounds-mainly those belonging to anthraquinones and phenylpropanoids (corresponding peak numbers in the parentheses): emodin-glucoside (29), torachrysone-hexoside (32), emodin-glucoside (33), emodin-8-O-(6 -O-malonyl)-glucoside (34), unknown torachrysone derivative (35), emodin bianthrone-hexose-(malonic acid)-hexose (38), hydropiperoside (39), and vanicoside B (48)-were abundant only in the 60% acetone extract, while being observed only in trace amounts in the 40% EtOH or in 25% EtOH. HMDB ID: The Human Metabolome Database, Physcion*-observed only in the positive mode.…”
Section: Hplc/dad/esi-hr-tof-ms Qualitative and Quantitative Analysismentioning
confidence: 99%
“…It is stronger than other extracts and stimulated fibroblasts proliferation and migration, which may be related to its highest content of resveratrol and the appropriate composition of procyanidins in it. Both resveratrol and procyanidins have proven immunomodulatory, anti-inflammatory, antioxidant, and antibacterial activity, positively influencing the prevention or treatment of periodontal diseases [34][35][36]. These proven effects of compounds that are present in the 25% EtOH extract may have additional benefits in the treatment of wounds where inflammation, oxidation, modulation of signal transmission, and other mechanisms are important parts of a healthy healing process.…”
Section: Total Polyphenols and Tannins Contentmentioning
confidence: 99%
“…However, to the best of our knowledge, it is not yet clear whether BQ123 directly regulates immune cell functions and alleviates allergic lung inflammation. In terms of acute inflammatory disease, it is important to reverse the established inflammation, in addition to exerting preventive effects (66). Therefore, the effect of BQ123 on the immune mechanism in the treatment of inflammatory diseases needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Procyanidins are major found in dark-colored fruits including cherry, grape, pomegranate, and blueberry (Ho et al, 2020). As antioxidant, anticancer, antibacterial, and anti-diabetic, procyanidins attract attention in the field of food and pharmacology (Li et al, 2021;Nawrot-Hadzik et al, 2021) Studies showed that the consumption of procyanidin-rich foods can lower the incidence of inflammatory diseases (Williams et al, 2004). Procyanidins (200-400 mg/kg) can inhibit XO activity and reduce serum uric acid levels in hyperuricemia mice in a dose-dependent manner (Wang et al, 2004).…”
Section: Procyanidinsmentioning
confidence: 99%